"Delightfully Feminine, Yet Practical": Circumlocution in Vietnam-Era Recruitment Brochures. Issue 2 (3rd April 2018) - Leuschen, Kathleen T.
Abstract : During the Vietnam era, the military recruited women by appropriating feminist language and simultaneously employing depictions of traditionally conservative feminine ideals. Using a rhetoric of circumlocution to yoke together these two contradictory images, military recruitment rhetoric ultimately reinstated women's subordinate status.